2020
DOI: 10.1093/mnras/staa775
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ram-pressure stripping on dwarf galaxies

Abstract: Ram-pressure stripping (RPS) is a well observed phenomenon of massive spiral galaxies passing through the hot intra-cluster medium (ICM) of galaxy clusters. For dwarf galaxies (DGs) within a cluster, the transformation from gaseous to gas-poor systems by RPS is not easily observed and must happen in the outskirts of clusters. In a few objects in close by galaxy clusters and the field, RPS has been observed. Since cluster early-type DGs also show a large variety of internal structures (unexpected central gas re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 67 publications
(106 reference statements)
3
32
0
Order By: Relevance
“…The lack of any stellar component seen in the optical bands associated with the star-forming complexes in the tail and their Hα-to-FUV colours strongly suggests that these are very recent objects ( 20 Myr) formed within the gas stripped during the interaction. The typical Hα luminosity of the HII regions formed within the tail is 10 37 erg s −1 , thus 1-2 orders of magnitude below the mean luminosity of the star-forming complexes measured in jellyfish galaxies during the GASP survey (Poggianti et al 2019); this is consistent with the predictions of the simulations of Tonnesen & Cen (2012) and Steyrleithner et al (2020). This difference is probably related to the limited angular resolution of the GASP data (FWHM ∼ 800 pc) for galaxies at a mean redshift of z ∼ 0.05, which does not enable us to resolve individual HII regions whose typical size is D eq 400 pc (Rousseau-Nepton et al 2018).…”
Section: Star Formation In the Stripped Gassupporting
confidence: 85%
See 1 more Smart Citation
“…The lack of any stellar component seen in the optical bands associated with the star-forming complexes in the tail and their Hα-to-FUV colours strongly suggests that these are very recent objects ( 20 Myr) formed within the gas stripped during the interaction. The typical Hα luminosity of the HII regions formed within the tail is 10 37 erg s −1 , thus 1-2 orders of magnitude below the mean luminosity of the star-forming complexes measured in jellyfish galaxies during the GASP survey (Poggianti et al 2019); this is consistent with the predictions of the simulations of Tonnesen & Cen (2012) and Steyrleithner et al (2020). This difference is probably related to the limited angular resolution of the GASP data (FWHM ∼ 800 pc) for galaxies at a mean redshift of z ∼ 0.05, which does not enable us to resolve individual HII regions whose typical size is D eq 400 pc (Rousseau-Nepton et al 2018).…”
Section: Star Formation In the Stripped Gassupporting
confidence: 85%
“…On the contrary, in the leading side of the disc the gas is totally removed on short timescales, totally quenching the activity after ∼50-100 Myr, as estimated from the SED fitting analysis of IC 3476. The star formation activity of the disc at galactocentric distances 9 kpc, which corresponds to the activity observed in the extended UV discs of unperturbed systems, drastically drops once the loosely bound gas is removed during the interaction, while it begins at small rates (SFR 0.01 M yr −1 ) 11 in the tail (Steyrleithner et al 2020) once the stripped gas cools and collapses into giant molecular clouds after ∼150 Myr (see Fig. 20).…”
Section: Gas Phases In the Tailmentioning
confidence: 86%
“…To which extent star formation is a common phenomenon in rampressure stripped tails is still under debate (Hester et al 2010;Fumagalli et al 2011;Kenney et al 2014;Boissier et al 2012;Boselli et al 2016;Fossati et al 2016;Gullieuszik et al 2017;Poggianti et al 2019;Bianconi et al 2020). One hint may come from the study by Steyrleithner et al (2020) in which they found via numerical simulations of ram-pressure stripped dwarf galaxies that obviously high relative velocities with respect to the ICM are necessary to sufficiently dissolve massive clouds, which remain gravitationally bound and are capable of cooling, collapsing, and forming star clusters.…”
Section: Discussionmentioning
confidence: 99%
“…10 for two densities. Moreover, the Kenney et al (2014) formula may correspond to an ideal situation, but the formation of star clusters is not necessarily a continuous function of the distance from the stripping event, as found in the simulations of Steyrleithner et al (2020) in which star formation sets in not immediately after the stripping event but in the stream behind.…”
Section: Gradients Along the Tailmentioning
confidence: 99%